Women supporting women : the role of doulas in South African birth stories - Abramovitz, Carly (University of Cape Town, 2014)
The medical and psychological benefits of birth companions, or doulas have been well documented over the last thirty years. This qualitative investigation provides, through the textured accounts of doulas and doula clients, insight into the nature of doula support.